POBOLJŠANJE TRAJNOSTI I KVALITETA MEXIČKIH LIMETA KROZ TRETMAN Γ-AMINOBUTERIČNOM KISELINOM - Assar, Pedram; Taghipour, Leila; Bagherian, Seyed Ali Akbar (Journal of Agricultural Sciences (Belgrade), 2025)
The key factors limiting the postharvest shelf life of limes are weight loss, rapid peel discoloration, and the degradation of their green color, which significantly reduces their market value. Mexican lime, a citrus fruit of considerable economic and nutritional importance, was evaluated for the effects of γ-aminobutyric acid (GABA) immersion on postharvest quality and storage life. Fruits were treated with GABA solutions (0, 4, 8, or 12 mM) and stored at 7 °C with 80 ± 5% relative humidity for 30 days. Measurements of fruit weight loss, total soluble solids (TSS), titratable acidity (TA), taste index (TSS/TA ratio), ascorbic acid content in juice, and rind pigments (chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids) were conducted every 10 days. GABA treatment, particularly at higher concentrations, significantly reduced weight loss and slowed TSS increases while enhancing TA and ascorbic acid levels. By the end of storage, treated fruits exhibited higher organic acid levels and a more desirable taste index, as indicated by a reduced TSS/TA ratio. Additionally, GABA treatments preserved higher chlorophyll levels for up to 20 days and delayed carotenoid accumulation, effectively slowing peel yellowing. The 8 mM concentration was the most effective in maintaining postharvest quality. These findings demonstrate that GABA can enhance the storage life and quality of Mexican lime, providing a promising strategy to minimize postharvest losses and boost economic value.